Peningkatan Kualitas Ikan Koi (Cyprinus carpio) di Kelompok PBC Fish Farm di Kecamatan Cisaat, Sukabumi - Yuli Andriani; Asri Peni Wulandari; Rusky Intan Pratama; Irfan Zidni (Institut Pertanian Bogor, 2019)
Various ornamental fish, such as koi and comet is a mainstay commodity from Nagrak Village, Cisaat District, Sukabumi Regency, West Java. The ornamental fish farmers in this village have been grouped in the form of pokdakan called “Pokdakan PBC Fish Farm”, which is chaired by Ikral Panutan. The main problem faced by members of this group is the color of the ornamental fish which still in low grade in quality. The purpose of this activity was to improve the quality of koi ornamental fish by using additional powder feed spirulina so that it can give added value to the production of ornamental fish produced. Community empowerment activities have been conducted for 4 months from July to October 2016. Steps of implementation include: 1) Socialization and initiation stage; 2) Training about fish culture management, spirulina culture method and feeding method using discussion method and demonstration plots; and 3) Evaluation and monitoring phase. The results obtained are generally these activities get the response and good results from the extension participants, as evidenced by the ability of farmers in cultured spirulina henceforth be applied as a mixture of fish feed can result in improved color quality of koi. Use of spirulina powder feed additional material on Cyprinus carpio of PBC Fish Farm proven to improve color quality, and provide value-added economy by 50–100 with the selling price ranging from IDR 3.000, per head to IDR 4.500–6.000 per tail.